PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA KEKERASAN SEKSUAL DALAM PERSPEKTIF UNDANG UNDANG NOMOR 12 TAHUN 2022 - Usup, Sitti Khairunnisah (Ensiklopedia Education Review, 2025)
Abstract: The Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS) enactment is an important step by the state in legally addressing the issue. This law represents a legal reform that places victims as subjects who must be fully protected. UU TPKS introduces a new approach in handling cases of sexual violence, emphasizing the principle of recovery for victims—physically, psychologically, and socially. Based also on Sexual Violence Crimes Article 1 Law No. 12 of, this issue is further regulated in Law No. 23 of 2002 on Child Protection Article 81 paragraph (1). In terms of legal protection supplied to the sexual violence’s victims, they are protected and entitled to their rights based on Article 5 of Law No. 31 of 2014.Keywords: Legal Protection, Victim, Sexual Violen